-3w+23=7(w+9)=

Simple and best practice solution for -3w+23=7(w+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3w+23=7(w+9)= equation:



-3w+23=7(w+9)=
We move all terms to the left:
-3w+23-(7(w+9))=0
We calculate terms in parentheses: -(7(w+9)), so:
7(w+9)
We multiply parentheses
7w+63
Back to the equation:
-(7w+63)
We get rid of parentheses
-3w-7w-63+23=0
We add all the numbers together, and all the variables
-10w-40=0
We move all terms containing w to the left, all other terms to the right
-10w=40
w=40/-10
w=-4

See similar equations:

| -97x=-5 | | 14=x*0.30 | | 1/3w=8 | | Y=4x-1;x=10 | | 3x+3x=45 | | w/10=3 | | 5(2x+3)+4(-4+6x)=(-16+35x) | | 35=-9x+9 | | 7(u+3)=28 | | 3x-30=20+5x | | 2.4x-4.1-3.7x=-1.3x-4.1 | | Y=8x;x=3 | | x-4/18=2/x+1 | | 24q=144 | | 5(2n+3)=6(9n+8)+2 | | 2x+6-1/3+1=6 | | 24=x*0.4 | | 4x+16=8x–20 | | Y=-5+(6x2) | | 7/3=2r-5/6r | | 1/9x=118 | | 24=-8+x | | 5y^2+4y-240=0 | | 25.92=x+.8x | | 2n^2+6n-340=0 | | 2(2n+5)=9(8n+6)+1 | | y=2(1/2)+9 | | -12+6=3x-6 | | -3x+5x=9+5x | | -5+6x=-x+9 | | -2-13.8=8x-(6x | | 60+2y=120 |

Equations solver categories